A Global Perspective of Vibrio Species and Associated Diseases: Three-Decade Meta-Synthesis of Research Advancement. (May 2022) - Onohuean, Hope; Agwu, Ezera; Nwodo, UU
Outbreaks of Vibrio infections have a long history of global public health concern and threat to the aquaculture industry. This 3-decade (1990-2019) meta-synthesis of global research progress in Vibrio species and associated disease outbreaks was undertaken to generate the knowledge needed to design effective interventions with policy implications. Using PRISMA protocol, we obtained data on the online version of the Institute for Scientific Information (ISI), Web of Science (WOS), and Scopus from January 1990 to September 2021 by title search of the keywords " Vibrio species OR Vibrio spp. OR vibriosis." On the 3-decade survey, the result has shown that a total of 776 publications document types were published on the subject, with an average of 24.25 ± 13.6 published documents per year with an annual growth rate of 4.71%. The year 2020 recorded the highest output of 52 published documents accounting for 6.70% of the total. The most prolific author, Blanch A., published 12 articles on the subject and has received citations of 1003 with an h-index of 10. While the most global cited paper author is the journal of J. Bacteriol (Bassler et al), receiving total citation (TC) (550) and per Year (22). The top active corresponding authors country is the United States of America with (92) articles, freq. 12.40%; TC of 3103. The observations in this study, such as the collaborations network map, and index, which have outlined a big difference between countries based on economic status, have underscored the need for a sustained research mentorship program that can define future policies.